Learning Strategies Used By A Student Of SMP Muhammadiyah 1 Surakarta To Master Speaking Skill (A Case Study) - Insyah, Wasilatul (2012)
This research studies learning strategies used by an individual student, S,in mastering English especially for speaking skill. The type of the research is a case study which aims to describe S's learning strategies in mastering speaking skill. The method of collecting the data is interview, observation, and documentation. The data are taken from the subject of the research in the form of field notes, interview, and document. The result of the research shows that S uses three kinds of learning strategies: metacognitive, cognitive and social-affective. Her metacognitive strategies, cover; advance organizer, directed attention, selective attention, self-management, and functional planning.While her cognitive strategies, cover; repetition, resourcing, note-taking,imagery, and elaboration. The last, the subject uses both of types of social-affective strategies. They arecooperation and question for clarification. Each of thosestrategies modifies each other. Totally she applies twelve strategies in mastering speaking skill. Most of learning strategies employed by S are full of consciousness. As a junior high school student, she likes applying these strategies in which on that occasion English is a foreign language that needs full concentration and awareness. Thus, the writer can conclude that three kinds of strategies, mostly for cognitive and metacognitive which apply consciousness in learning, help the students much, especially for S in mastering speaking skill.